I will be complete : a memoir - Gold, Glen David, 1964- (Alfred A. Knopf, 2018)
"From the best-selling author of Carter Beats the Devil and Sunnyside, a big-hearted memoir told in three parts: about growing up in the wake of the destructive choices of an extremely unconventional mother. Glen David Gold was raised rich, briefly, in southern California at the end of the go-go 1960s. But his father's fortune disappears, his parents divorce, and Glen falls out of his well-curated life and into San Francisco at the epicenter of the Me Decade: the inimitable '70s. Gold grows up with his mother, among con men and get-rich schemes. Then, one afternoon when he's twelve, she moves to New York without telling him, leaving him to fend for himself. I Will Be Complete is the story of how Gold copes, honing a keen wit and learning how to fill in the emotional gaps: "I feel love and then it's like I'm driving on black ice with no contact against the road." He leads us though his early salvation at boarding school; his dream job at an independent bookstore in Los Angeles in 1983; a punk rock riot; a romance with a femme fatale to the soundtrack of R.E.M.; and his attempts to forge a career as a writer. Along the way, Gold becomes increasingly estranged from both his parents--his mother lives with her soulmate, a man who threatens to kill her, and his father is remarried (for money, he explains) with young children. Clear-eyed and heart-breaking, Gold's story ultimately speaks to everyone who has struggled with the complexity of parental bonds by searching for--and finding--autonomy"--